The Impact of Mobile Health Education on Adolescent Girls’ Knowledge of Child Marriage - Dian Purnama Yanti; Nurlathifah N Yusuf; Baiq Disnalia Siswari (Pubfine Media Group, 2026)
Introduction: Child marriage (early marriage) refers to a marital union in which one or both partners are still categorized as children or adolescents under the age of 19 years. Child marriage can lead to negative consequences for both physical and psychological health. Considering that adolescents are digital natives, the utilization of mobile health technology offers a relevant, interactive, and easily accessible educational solution. This study aimed to examine the effect of mobile health–based education on adolescent girls’ knowledge of child marriage. Methods: This study employed a pre-experimental one-group pretest–posttest design involving 43 adolescent girls selected using stratified random sampling. Data were analyzed using the Wilcoxon Signed-Rank Test. Results: Prior to the health education intervention, most adolescent girls demonstrated a low level of knowledge, with 40 respondents (93.02%). After receiving mobile health–based education, the majority showed a good level of knowledge, with 36 respondents (83.72%). Statistical analysis indicated a significant difference in knowledge levels before and after the intervention (p = 0.000; p < 0.05). Conclusion: Mobile health–based health education had a significant effect on improving adolescent girls’ knowledge of child marriage.